Prince of Physicians - ChaudharyEhtshamAzmat,AbdulBasitShahVardag,RabiaAnjum,AhmedMoosaKazi,FarazIftikhar,MohammadAmmad-Ud-Din,HamzahSaleem, ChaudharyEhtshamAzmat,AbdulBasitShahVardag,RabiaAnjum,AhmedMoosaKazi,FarazIftikhar,MohammadAmmad-Ud-Din,HamzahSaleem (Journal of Rawalpindi Medical College, 2018)
Everyone is familiar with Hippocrates, Plato and Aristotle. Their works and their achievements. Ask about the contribution of the greats of Medicine who followed many centuries later, in the Islamic era and many would simply profess their ignorance